An Analysis of The Variety of Communication Used by Kasta and Non-Kasta People in Kenderan Village - I Dewa Ayu Melani Wulandari (STKIP AGAMA HINDU SINGARAJA, 2022)
This study aims to be able to analyze and describe the diversity of speech of Kasta and non-Kasta people in the village of Kenderan. This study uses a qualitative analysis method that can support and continue this research and shows the variety of speech of Kasta and non-Kasta people. The results obtained from this study are 1. Kasta people in Kenderan Village are very active and fluent in speaking. 2. Kasta people in Kenderan village show more verbal skills when speaking compared to non-Kasta people. 3. There are many differences in the language used by Kasta people in Kenderan village during communication/conversation with non-Kasta people. Still, even though they are different, they have the same meaning. 4. There are a variety of words that include a variety of dictions between Kasta and non-Kasta people in the village of Kenderan. 5. There are norms that Kasta people must obey, which is a culture not to speak harshly. There are two theories used in this study, namely the theory of Marshall (1994) and Fox (1974), which relates to the topic of this research